European Registry on Helicobacter pylori management: Single‐capsule bismuth quadruple therapy is effective in real‐world clinical practice. Issue 1 (11th February 2021) - Nyssen, Olga P.; Perez‐Aisa, Angeles; Castro‐Fernandez, Manuel; Pellicano, Rinaldo; Huguet, Jose M.; Rodrigo, Luis; Ortuñ, Juan; o,; Gomez‐Rodriguez, Blas J.; Pinto, Ricardo M.; Areia, Miguel; Perona, Monica; et al.
Abstract: Background: There has been resurgence in the use of bismuth quadruple therapy (proton pump inhibitor, bismuth, tetracycline and metronidazole) for treating Helicobacter pylori infection thanks to a three‐in‐one single‐capsule formulation. Objective: To evaluate the effectiveness and safety of the single‐capsule bismuth quadruple therapy. Methods: Data were collected in a multicentre, prospective registry of the clinical practice of gastroenterologists on the management of H. pylori infection, where patients were registered at the Asociación Española de Gastroenterologia REDCap database on an electronic case report form until January 2020. Effectiveness by modified intention‐to‐treat and per‐protocol as well as multivariable analysis were performed. Independent factors evaluated were: age, gender, indication, compliance, proton pump inhibitor dose and treatment line. Results: Finally, 2100 patients were prescribed single‐capsule bismuth quadruple therapy following the technical sheet (i.e., three capsules every 6 h for 10 days). The majority of these patients were naive (64%), with an average age of 50 years, 64% women and 16% with peptic ulcer. An overall modified intention‐to‐treat effectiveness of 92% was achieved. Eradication was over 90% in first‐line treatment (95% modified intention‐to‐treat, n = 1166), and this was maintained as a rescue therapy, both in second (89% modified intention‐to‐treat, n = 375) and subsequent lines of therapy (third to sixth line: 92% modified intention‐to‐treat, n = 236). Compliance was the factor most closely associated with treatment effectiveness. Adverse events were generally mild to moderate, and 3% of patients reported a severe adverse event, leading to discontinuation of treatment in 1.7% of cases. Conclusions: Single‐capsule bismuth quadruple therapy achieved H. pylori eradication in approximately 90% of patients in real‐world clinical practice, both as a first‐line and rescue treatment, with good compliance and a favourable safety profile. Key Summary: The development of a three‐in‐one single‐capsule formulation has led to a resurgence in the use of bismuth quadruple therapy (BQT) to treat Helicobacter pylori infection. In the largest study carried out to date, the effectiveness of single‐capsule BQT was optimal both as a firstline and as a rescue therapy. Compliance was the factor most closely associated with treatment effectiveness. Single‐capsule BQT eradicates H . pylori in approximately 90% of patients in real‐world clinical practice, with a favourable safety profile.